2002
DOI: 10.1177/000331970205300209
|View full text |Cite
|
Sign up to set email alerts
|

Association of Carotid Artery Intima-Media Thickness with Complex Aortic Atherosclerosis in Patients with Recent Stroke

Abstract: This study was undertaken to determine whether carotid intima-media thickness can predict complex aortic atherosclerosis. A retrospective review was conducted of 64 consecutive patients who underwent transesophageal echocardiography and carotid ultrasonography for evaluation of recent ischemic stroke at MCP Hahnemann University, Medical College of Pennsylvania Hospital between January 1, 1999, and December 31, 1999. The mean age was 65+/-14 years and 59% of the patients were women. Thirty-nine patients (61%) h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…In a previous study, we demonstrated that a normal carotid IMT excluded aortic high-risk sources of cerebral embolism, such as thrombi or plaques Ն4 mm, thus making transesophageal echocardiography (TEE) dispensable for assessment of the aorta. 6 However, in concordance with others, 7 positive predictive values were low.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…In a previous study, we demonstrated that a normal carotid IMT excluded aortic high-risk sources of cerebral embolism, such as thrombi or plaques Ն4 mm, thus making transesophageal echocardiography (TEE) dispensable for assessment of the aorta. 6 However, in concordance with others, 7 positive predictive values were low.…”
supporting
confidence: 84%
“…Cardiovascular risk factors were prospectively documented and defined as described previously. 7 Infarct etiology was classified according to the Trial of Org 10172 in Acute Stroke Treatment (TOAST) criteria in each patient after completion of the diagnostic work-up. 9 …”
Section: Study Population and Cardiovascular Risk Factorsmentioning
confidence: 99%
“…Though we did not directly visualize the atheromatous burden of the aortic arch, we assessed carotid IMT by means of ultrasound. An enlarged IMT independently predicts aortic plaques and complex aortic atherosclerosis [21,22]. In a previous study including patients from the present analysis, we found that aortic atherosclerosis alone does not account for the high risk from stenting in older patients, but that both age and aortic atherosclerosis independently predict periprocedural ischemic events [15].…”
Section: Discussionmentioning
confidence: 54%
“…Our findings are consistent with recent studies suggesting the use of CIMT testing for the exclusion of significant aortic atheroma. 8,9,17 In a prospective study, Harloff et al reported that use of CIMT testing achieved a negative predictive value of 92% for the detection of complex aortic atheroma. 9 Complex aortic plaques are particularly important to exclude because they are associated with a increased risk of recurrent stroke and may warrant therapy with statins or warfarin.…”
Section: Discussionmentioning
confidence: 99%